2019
DOI: 10.1186/s41606-019-0037-3
|View full text |Cite
|
Sign up to set email alerts
|

Disorders of Arousal in adults: new diagnostic tools for clinical practice

Abstract: Disorders of Arousal (DOA) are mental and motor behaviors arising from NREM sleep. They comprise a spectrum of manifestations of increasing intensity from confusional arousals to sleep terrors to sleepwalking. Although DOA in childhood are usually harmless, in adulthood they are often associated with injurious or violent behaviors to the patient or others. Driving motor vehicles, suspected suicide, and even homicide or attempted homicide have been described during sleepwalking in adults. Furthermore, adult DOA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 59 publications
(75 reference statements)
0
20
0
1
Order By: Relevance
“…Arousals and microarousals are also considered as slow-wave sleep interruptions, which has been studied in detail in disorders of arousals such as confusional arousals, sleepwalking and sleep terrors. Hypersynchronous delta wave activity was the first EEG marker to be described in relation to disorders of arousal episodes though further studies demonstrated low specificity for the same in the diagnosis of disorders of arousal [6] .…”
Section: Discussionmentioning
confidence: 99%
“…Arousals and microarousals are also considered as slow-wave sleep interruptions, which has been studied in detail in disorders of arousals such as confusional arousals, sleepwalking and sleep terrors. Hypersynchronous delta wave activity was the first EEG marker to be described in relation to disorders of arousal episodes though further studies demonstrated low specificity for the same in the diagnosis of disorders of arousal [6] .…”
Section: Discussionmentioning
confidence: 99%
“…They can also occur out of stage N2, especially in adults [ 7 ]. Disorders of arousal are common phenomena in childhood, tend to decrease with age [ 12 ], and become less frequent after the age of five [ 13 ]. However, NREM parasomnias can also persist into adulthood and in some cases can even start de novo in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep terrors emerge from stage 3 NREM sleep with shouting and high autonomic changes. In contrast to sleep terror, in nightmares no confusion or disorientation is present, and the highly disturbing dream content frequently contrasts strikingly with relatively minor autonomic activation (except for the increase of autonomic tone before the awakenings) and no acting out of the nightmare (24,132). Hallucinations and sleep paralysis may be described as "nightmares, " but they specifically occur at sleep onset and offset, and the paralysis affects the whole body (115).…”
Section: Differential Diagnosismentioning
confidence: 99%
“…Upside-down triangles represent recorded episode(s) during nocturnal videopolysomnography. [Modified with permissions from ( 23 ) and ( 24 ) under Creative Commons Attribution 4.0 International License— http://creativecommons.org/licenses/by/4.0/ ].…”
Section: Oneiric Stupor In Agrypnia Excitatamentioning
confidence: 99%